Integrasi Pendekatan Pembelajaran Adaptif dan Teknologi Interaktif untuk Mengoptimalkan Proses Belajar Mahasiswa di Lingkungan Perguruan Tinggi Digital - Ikhwan Pujiono; Viviane Manoppo; Rendy Bagus Pratama (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The transformation of higher education towards the digital era demands innovation in learning methods that can accommodate the diversity of student characteristics. This article examines the integration of adaptive learning approaches with interactive technology as a solution for optimizing the learning process in digital universities. Through a literature study method, this research analyzes various scientific sources to understand the concepts, implementation, and impact of integrating these two approaches. The results of the study show that adaptive learning reinforced with interactive technology can significantly improve learning personalization, student engagement, and learning outcomes. This integration allows for the adjustment of content, pace, and learning methods based on individual student needs, while utilizing various interactive media to enhance the learning experience. The main challenges in implementation include infrastructure limitations, human resource readiness, and the need for a learning paradigm shift. However, with the right implementation strategies and adequate institutional support, the integration of adaptive learning and interactive technology can be the key to the success of higher education transformation in the digital era.